The Changing Political Map of India After Independence: Focusing on the Emergence of New States. - Sonali Munda; Dr. Siddhartha Chatterjee (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
India's political map has undergone a remarkable transformation since independence in 1947. This paper explores the emergence of new states as a key driver of this change. It examines the historical context, factors influencing state formation, and the impacts on India's socio-political landscape. The paper argues that while language played a crucial role, cultural identity, administrative needs, and political considerations also shaped the process. The emergence of new states has had a mixed impact, promoting regional representation but also presenting challenges in development and inter-state relations. Finally, it analyzes the ongoing dynamics and the need for India's federal structure to adapt to accommodate the aspirations of its constituent states.